Quickest Transshipment in the Prioritized Evacuation Network - Adhikari, Iswar Mani (Kaumodaki: Journal of Multidisciplinary Studies, 2023)
Flow maximization, time minimization, and cost minimization are three main aspects of mathematical optimization problems. The evacuation planning problems are about flow maximization and/or time minimization problems in different dynamic evacuation networks. The quickest transshipment problem in such a network is to send exactly the right amount of flow out of each source and into each sink in the minimum overall time. In evacuation planning problems, the term flow stands for either the evacuees or the evacuees carrying vehicles. Here, we use the quickest transshipment strategy in a prioritized evacuation network. It consists of a collection and an assignment sub-network as the primary and secondary sub-networks, respectively. Pick-up locations are prioritized in the collection network. By treating such pick-up locations as sources, the available set of transit buses is assigned in the assignment sub-network to shift the evacuees to the sinks to achieve the quickest transshipment. Such an evacuation planning strategy is better suited for the simultaneous collection, assignment, and evacuation process in the prioritized evacuation network.